Efektivitas Model Pembelajaran Quantum Teaching terhadap Hasil Belajar Fisika Siswa SMA Negeri Jayaloka - Umi Khusnul Khotimah; Tri Ariani; Ovilia Putri Utami Gumay (SPEJ (Science and Physic Education Journal), 2018)
The purpose of this study is to determine whether the model of effective teaching quantum teaching used in physics learning in SMA Negeri Jayaloka academic year 2017/2018. The methoud used is quasi eksperiment or pseudoexpansion. The type of research is quasiexperimental research, with the design used is one group pretest and posttest design. The population in this study is all students of class X SMA Negeri Jayaloka academic year 2017/2018. And as the sample is the class X.I which amounted to32 student consisting of 17 male students and15 famale students taken at random. Data retrieval is done by test and non test technique. The collected data were analyzed using ttest at significant level = 0,05 obtained by t value 4,69 more than t table 1,69. So it can be concluded that student learning outcomes by using the modelof learning Quantum Teaching significant completion. Student learning activites in the learning process in the active category. While student response after following learning in good category. Keywords: Quantum Teaching Learning Model, Learning Outcomes,